Sm-Nd isotopic constraints on the metadolerite dykes from Western Dharwar Craton, Southern India: implications on the evolution of Archean subcontinental lithospheric mantle - Silpa, A. S.; Satish-Kumar, M.; Takahashi, T.; Kamei, A. (Frontiers in Earth Science, 2023)
Introduction: Metadolerite dykes in the Western Dharwar Craton represent the oldest generation of mafic dyke swarms in the craton. The emplacement of these dykes after a period of crust building activity and komatiite volcanism, helps to understand the evolution of Subcontinental Lithospheric Mantle (SCLM) and Archean dynamics. Methods: We report whole rock major, trace element geochemistry and Sr-Nd isotope characteristics for this weakly metamorphosed suite of dykes. Remnant igneous textures and mineralogy are well preserved. Results: The trace and rare earth element concentrations and an overall flat pattern suggests depleted mantle source for these dykes. Three groups are primarily identified: Group one with initial 87Sr/86Sr ratios varying between 0.70041 and 0.70102, Group two dykes and Group three dykes with initial ratios 0.70045–0.70154, and 0.70041–0.70153 respectively. Group one dykes show a good Rb-Sr isochron relationship and an errorchron age of ca. 3,003 ± 102 Ma is obtained. The initial 143Nd/144Nd ratios varies from 0.508,245 to 0.509,172. The epsilon Nd values are mostly negative, ranging between −12 and +5. Group one and two show an epsilon Nd value ranging between −1 and +5 and 0.1 to +5 respectively and group three varies between −0.5 and −12. Discussion: The geochemical characteristics suggest that the group one dykes are derived from a homogenous depleted SCLM source, group two formed by a lower degree of partial melting of a source mantle with enriched components. Group three may have formed from a progressively enriched group one source. All these dykes can be considered as exposed remnants of feeders for the greenstone volcanism in the Western Dharwar Craton.